Acute effect of whole body vibration on isometric strength, squat jump, and flexibility in well-trained combat athletes - Kurt, Cem; Pekünlü, Ekim (Biology of Sport, 2015)
The purpose of this study was to investigate the effect of whole body vibration (WBV) training on maximal strength, squat jump, and flexibility of well-trained combat athletes. Twelve female and 8 male combat athletes (age: 22.8 ± 3.1 years, mass: 65.4 ± 10.7 kg, height: 168.8 ± 8.8 cm, training experience: 11.6 ± 4.7 years, training volume: 9.3 ± 2.8 hours/week) participated in this study. The study consisted of three sessions separated by 48 hours. The first session was conducted for familiarization. In the subsequent two sessions, participants performed WBV or sham intervention in a randomized, balanced order. During WBV intervention, four isometric exercises were performed (26 Hz, 4 mm). During the sham intervention, participants performed the same WBV intervention without vibration treatment (0 Hz, 0 mm). Hand grip, squat jump, trunk flexion, and isometric leg strength tests were performed after each intervention. The results of a two-factor (pre-post[2] × intervention[2]) repeated measures ANOVA revealed a significant interaction (p = 0.018) of pre-post × intervention only for the hand grip test, indicating a significant performance increase of moderate effect (net increase of 2.48%, d = 0.61) after WBV intervention. Squat jump, trunk flexion, and isometric leg strength performances were not affected by WBV. In conclusion, the WBV protocol used in this study potentiated hand grip performance, but did not enhance squat jump, trunk flexion, or isometric leg strength in well-trained combat athletes.